John Dewey. Una perspectiva de su concepción de la verdad - Teliz, Ronald (2007)
“John Dewey. A perspective of his Concept of Truth”. Rorty proposes his view as being an heir of pragmatism, such as J. Dewey’s, emphasizing that it stems, among other things, from the pragmatist notion of truth. Differing from many of Rorty’s ideas, I attempt to expound some notions I deem relevant in J. Dewey’s philosophy, and especially discuss some aspects of his conceptof truth. I plan to show that Dewey’s pragmatism takes up some traces of our everyday concept of truth, related to correspondence, but that this does not imply an engagement with a robust notion of truth. At the same time, I believe that the acceptance of such traces, although it does not suppose a definition or clear explanation regarding the “content” of truth, suffices to distinguish between truth’s normative aspect and any justificationist view that may operate as knowledge’s epistemic support.